General Dental Students' Views About the Ethics Level in Education, Research, and Provision of Dental Services - Leila Bazrafkan; Masoud Yousefi; Javad Kojuri; Mohammad Ansarizadeh; Habibolah Rezaei (Shiraz University of Medical Sciences, 2024)
Background: The current study examines general dental students' views about the ethics level in education, research, and provision of dental services.Methods: This descriptive cross-sectional study was performed on all general dental students at Yasuj University of Medical Sciences selected in the census. The researcher-made questionnaire was prepared online with PorsLine. In this questionnaire, examples of observing or not observing ethics in education, research, and provision of dental services by faculty members were presented to the dental students. Finally, all collected data were analyzed by SPSS software version 26.Results: 47 students participated in the current study. The participant's mean age was 25.95 with a standard deviation of 3.5. Results of the study showed that the mean and standard deviation of non-observance of ethics in education, the provision of dental services, and research were 3.05±0.9, 2.37±1.03, and 3.04±1.15, respectively.Conclusion: General dental students reported that the level of ethics in education, research, and provision of dental services by faculty members was unfavorable, so it is recommended that medical education courses related to ethics should be held for faculty members.